(3TQM GdJKHjJ YfO GdJHjjJs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3Cf jchf aYjdG efj aGYd ceG gh GdXGgQ hCf jchf HeYfi eaYhd dCfg jNHQ HGdEjMGA Edjg s
(3BNQgG (B:s
(3hGNJda Cgd GdWQjbI GdChdi gd YdegG GdfHj Udi Gddg Ydjg hSde Ce dG abGd s
(3CQLhRIs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B344s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds